Pengaruh Penambahan Pasir terhadap Tingkat Kepadatan dan Daya Dukung Tanah - Jihadakbar Jihadakbar; Adnan Adnan; Mustakim Mustakim (Pusat Riset dan Inovasi Nasional, 2024)
Land is one of the most important parts of a construction building. Soil strength is needed to support the load of a building. However, not all types of soil can be used directly to make construction buildings, one of which is peat soil in Sulobaja Village, Tobadak District, Central Mamuju Regency. So it is necessary to do soil improvement or soil stabilization in order to achieve the standard soil density value that is suitable for use for a construction building. From the results of testing the addition of sand to peat soil, the level of soil water content increased in a mixture of 5% and 10% sand, namely from the normal soil water content of 9.82% to 10.01% in a mixture of 5% sand and to 10.06% in the addition of 10% sand. Meanwhile, with the addition of 15% sand, the soil water content decreased to 8.22% and with the addition of sand, the degree of soil density increased from 84.11% to 86.06% with the addition of 5% sand, 89.36% with the addition of 10% sand, and to 93.50% with the addition of 15% sand, so it is known that the more sand is added, the higher the degree of soil density obtained.